Structural organization of bacterial ureases - Lisnyak, Yu; Martynov, A (Annals of Mechnikov’s Institute, 2020)
This brief review concerns the basic principles of structural organization of multi-subunit bacterial ureases and formation of their quaternary structure. Urease is a nickel-containing enzyme (urea amidohydrolase, ЕС 3.5.1.5) that catalyses the hydrolysis of urea to get ammonia and carbamate which then decomposes with water to get ammonia and carbon dioxide. Urease is produced by bacteria, fungi, yeast and plants. On the basis of similarities in amino acid sequences, ureases assumed to have a similar structure and conservative catalytic mechanism. Within past two decades bacterial ureases have gained much attention in research field as a virulence factor in human and animal infections. The first crystal structure of urease has been determined for that from Klebsiella aerogenes. The native enzyme consists of three subunits, UreA (α-chain), UreB (β-chain) and UreC (γ-chain), and contains four structural domains: two in α-chain (α-domain 1 and α-domain-2), one in β- and one in γ-chain. These three chains form a T-shaped heterotrimer αβγ. Three αβγ heterotrimers form quaternary complex (αβγ)3. In case of Helicobacter pilori, the analogous trimers of corresponding dimeric subunits (αβ)3 form tetrameric structure ((αβ)3)4 in which four trimers are situated at the vertexes of the regular triangle pyramid. Active center is located in α-domain 1 and contains two atoms of nickel coordinated by residues His134, His136, carboxylated Lys217, His 246, His272 and Asp360, as well as residues involved in binding (His219) and catalysis (His320). Active site is capped by a flap that controls substrate ingress to and product egress from the dinickel center. Urease requires accessory proteins (UreD, UreF, UreG and UreE) for the correct assembly of their Ni-containing metallocenters. The accessory proteins UreD, UreF, and UreG sequentially bind to the apoprotein (UreABC)3 to finally form (UreABC-UreDFG)3 activation complex. UreE metallochaperone delivers nickel ions to this complex, UreE and (UreDFG)3 are then released from the activated enzyme. An understanding of structural organization of bacterial ureases is the necessary factor in the studies of structure-function relationships of these enzymes, mechanisms of their enzyme and non-enzyme activity, in design of new safe and efficient enzyme inhibitors aimed to struggle with infectious diseases promoted by urease activity.